Las gramáticas de la ley : derecho, pluralismo y justicia - Webber, Jeremy H. A., 1958- (Pensamiento crítico/pensamiento utópico ;, 2017)
This work normatively theorizes legal pluralism and analyzes the interaction of the indigenous peoples of Canada and Australia with state law. Jeremy Webber develops in this work a normative theory of legal pluralism analyzing the interaction of the indigenous peoples of Canada and Australia with state law. Long ignored and oppressed, indigenous populations are an increasingly important part of numerous countries in the world that claim the right to their social and legal autonomy. The book examines the nature of historical encounters between indigenous societies and colonizing states, the foundations of their respective legal cultures and the potential that communication and intercultural judgment offer for the administration of justice in constitutively diverse societies.